Kesiapan Kantin di PTAIN Sumatera Barat Menuju Kantin Bersertifikasi Halal - Media Roza; Sabhamis Sabhamis; Nurhasnah Nurhasnah; Milya Sari (Natural Science, 2022)
UU No. 33 of 2014 concerning Halal Product Guarantee (JPH) is implemented mandatively starting in October 2019 of all products circulating in Indonesia, including food. Therefore, every business actor in the industry, restaurants, cafeterias or canteens must prepare themselves to carry out halal certification of the products being sold. This study aims to determine the readiness of the canteen at PTAIN West Sumatra towards a halal certified canteen. Canteen readiness can be seen from the canteen manager's knowledge of PTAIN regarding the JPH Law, the understanding of canteen managers at PTAIN on the halal guarantee system criteria, and the canteen manager's behavior at PTAIN towards Halal Critical Control Points. This type of research is field research using a combination of research (Mixed Method) using the Concurrent Triangulation Strategy model. The results showed that the average canteen manager's knowledge of the JPH Law was good, an understanding of good halal product guarantees, and good HCCP behavior. The level of canteen readiness to halal certified canteen at Imam Bonjol Padang UIN is 68.56%, the canteen at IAIN Batusangkar 73.76%, and the canteen at IAIN Bukittinggi 73.21%. It can be concluded that the readiness of the canteen at PTAIN West Sumatra towards the halal certified canteen is in the good category,and ready to go to the halal certified canteen